2016
DOI: 10.1093/heapro/daw068
|View full text |Cite
|
Sign up to set email alerts
|

Culture, management and finances as key aspects for healthy workplace initiatives

Abstract: The aim of this study was to qualitatively explore the barriers and enablers to implementing healthy workplace initiatives in a sample of workplaces based in Perth, Western Australia. In-depth interviews were conducted with representatives from 31 organizations representing small, medium and large businesses in the Perth metropolitan area which reported having healthy workplace initiatives. In total, 43 factors were mentioned as influencing the implementation of healthy workplace initiatives. Factors appearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…In general, workplace health culture was positively associated with all health-related outcomes, which supported several previous qualitative studies [5, 7, 27]. Variance analyses results showed that individual health culture, beneficial health effects of direct leaders, and health culture at the workplace level were all positively associated with the 3 health-related outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, workplace health culture was positively associated with all health-related outcomes, which supported several previous qualitative studies [5, 7, 27]. Variance analyses results showed that individual health culture, beneficial health effects of direct leaders, and health culture at the workplace level were all positively associated with the 3 health-related outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Golaszewski et al [6] presented a conceptual model for addressing the creation of supportive environments for worksite health promotion settings, and emphasized the importance of improving the cultural environment of workplaces for health promotion. Results of a qualitative study conducted in-depth interviews with representatives from 31 organizations representing small, medium and large businesses in Western Australia showed that improving health culture had an important impact on health promotion [7]. However, most existing studies lack support of convincing quantitative data [8].…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, no standardized tools for assessing knowledge, attitudes, practices and likelihood of action for workplace health implementation exists. However, our survey instrument is informed by an established theoretical framework [26,27] and years of research on workplace health promotion [3,[28][29][30][31][32][33]. In addition, we assessed the construct reliability and convergent validity using Cronbach's alpha and factor loadings, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to find a specific and validated survey that measured knowledge, attitudes and practices for WHP. Therefore, the second literature review focused on examining the components on the KAP conceptual framework (Figure 1) to better understand the barrier and enablers to implementing WHP [3,[28][29][30][31][32][33]. For a more detailed explanation of the questions included in the survey instrument, the scale of measure, and the concepts included, see Appendix A.…”
Section: Survey Instrumentmentioning
confidence: 99%
See 1 more Smart Citation